Quantifying frequency of use of methods of body mass loss in competing UK powerlifters. Issue 2 (June 2022) - Wood, T.J.; Wilson, L.J.; Curtis, C.
Abstract: Previous research in Powerlifting (PL) has qualitatively investigated rapid weight-loss (RWL) in PL athletes and body image, however limited research exists in quantifying such methods adopted in PL. This study aimed to assess the frequency of RWL methods are adopted by male and female PL athletes in the United Kingdom (UK) during competition preparation. A total of n = 37 ( n = 19 female, n = 18 male) competitive powerlifters completed an anonymous online questionnaire assessing RWL methods. A Chi-square cross tabulation was utilised to identify any significant differences between independent and dependent variables. Multiple regression analyses were then conducted to assess the contribution of biological sex and PL category on RWL methods. Commonly reported methods of weight loss were gradual dieting (49%), fluid restriction (46%), and water loading (51%). Differences between PL category (Junior, Open, Masters One) and adopting RWL were observed ( X 2 =4.220, p <0.05 ) . PL category was a predictor of undertaking RWL ( R 2 adj = 0.160, F (2, 34) = 4.429, p ≤ 0.05), whilst biological sex was a predictor of timeframe of undertaking RWL ( R 2 adj = 0.123, F (2, 34) = 3.534, p ≤ 0.05). RWL strategies are adopted by PL athletes in order to make weight for competition. Despite known effects of RWL on strength performance, limited research currently exists on these strategies specifically within PL, therefore this may be a consideration for future research. Practitioners working with PL athletes may wish to consider appropriate nutrition and weight loss strategies in preparation for PL competitions.